Analisis Kinerja Mesin Peniris Bawang Untuk Industri Makanan Skala Kecil - Dwy, Shera; Hermanto, Tino; Iswandi, Iswandi; Darianto, Darianto (CV. IRA PUBLISHING, 2025)
This study aims to analyze the performance of a fried onion draining machine designed for the needs of small-scale food industries. The machine operates using the principle of centrifugal force and is constructed with 304 stainless steel to ensure food safety and resistance to corrosion. Testing was conducted using variables such as rotation speed, draining time, and material capacity. Results show that the machine can reduce oil content in fried onions by 14.29% within 2 minutes, with a draining capacity of 50 kg per hour at 700 rpm. Energy efficiency achived was 35,49%, showing the potential for practical application of this machine in the UMKM environment. The use of this machine results in fried onions that are crispier, have a longer shelf life, and are processed more hygienically and efficiently. Further recommendations include design and operation system optimization to improve performance.